Aplikasi Sistem Pemesanan Travel Berbasis Android pada PT Kirana Anugerah Terindah - Wijaya, Sugeng Hadi; Handojo, Andreas; Andjarwirawan, Justinus (Jurnal Infra, 2015)
PT Kirana is a well-known travel agency in the city of Malang. The company provides several kinds of tour packages at affordable prices. Kirana Travel has several routes, among others: Surabaya, Mojokerto, Malang and Juanda. At this time, the existing business system is still manual, recording orders placed are still manual. The ordering is done over the phone, then the admin noted that customer address will be picked up. After noting all existing orders, admin notify the driver addresses will be picked up. Drivers do not know the best route to be taken. At the time of the operation of the fleet, the driver only has the addresses of customers who will be picked up one by one. Currently operates a fleet of office parties and customers usually do not know where the position of the current fleet.This application is created using eclipse program and phpMyAdmin as database storage system. The application is divided into three applications: application for customer, application for admin, and application for the fleet. Customer application used to perform the ordering. Admin application is used for schedule and order management. Fleet application used to see pick-up route.From the results of testing of applications, shows that this application can run well on mobile devices that use the operating system andorid. Because every customer will use mobile devices to do the ordering process. So Kirana Travel reservations will be easier in the future.